“‘Making Places to Live’: Native American Poetry Past and Present” - Larré, Lionel (Transatlantica, 2010)
Depuis 2006, Simone Pellerin (Université Paul Valéry, Montpellier 3) organise annuellement un colloque international sur les littératures amérindiennes. Le colloque, auquel participe des spécialistes de renom, est à chaque fois d’excellente tenue. En 2006, il était consacré à l’écrivain anishinaabe Gerald Vizenor, en sa présence, et donna naissance à un volume de la collection « Profils américains » (Gerald Vizenor, Simone Pellerin ed., Presses universitaires de la Méditerranée, 2008) contena. Since 2006, Simone Pellerin (Paul Valéry University, Montpellier 3) has held an annual international colloquium on Amerindian Literature. The colloquium, attended by renowned specialists, is always excellent. In 2006, he was dedicated to the anishinaabe writer Gerald Vizenor, in his presence, and gave rise to a volume of the ‘American Profils’ collection (Gerald Vizenor, Simone Pellerin ed., Mediterranean Academic Presses, 2008).